The role of Turkey in the second Armenian-Azerbaijani armed conflict over Nagorno-Karabakh as a reflection of continuity and change in its foreign policy - Ana Jović-Lazić (Međunarodni Problemi)
The article examines Turkey’s role in the conflict over Nagorno-Karabakh that erupted between Azerbaijan and Armenia in September 2020. It analyses how changes and continuity in Turkey’s foreign policy have influenced the conflict’s outcome, as well as the extent to which it has been exploited to fulfil Turkey’s foreign policy objectives. Thus, unlike most research on Nagorno-Karabakh, this article focuses on the role of one external actor, and not on the conflict itself or possible hypotheses for its resolution. The article’s special focus was influenced by the fact that Turkey’s participation resulted in a change in the long-standing status quo in Nagorno-Karabakh, allowing the situation to turn dramatically in Baku’s favour. Turkey, along with Russia, has emerged as one of the most important regional players in this conflict. This is the result of Turkey’s emphasised foreign policy ambitions, which were influenced by changes in its international security environment as well as changes in the country’s domestic policy. In any case, with its role in the second conflict in Nagorno-Karabakh, Turkey has once again shown its determination to pursue its foreign, and especially regional, policy independently and in accordance with its national interests, despite being a member of NATO.